Customer Complaint Handling Services at the Regional Public Company for Drinking Water (PERUMDA) Tirta Giri Nata Cirebon City - Marbella, Breenda; Widya, Widhi; Wulandari, Sri; Heryanto, Yanto (Riviera Publishing, 2024)
This research is based on the need for clean water, a vital human need. PERUMDA Tirta Giri Nata Cirebon City is a BUMD responsible for providing clean water in Cirebon City. It has a complaint service to handle various customer problems. This study aims to discover the Customer Complaint Handling Service at the Tirta Giri Nata Regional Public Company (PERUMDA) Tirta Giri Nata, Cirebon City. The research method is qualitative descriptive, using data collection techniques through interviews, observations, and documentation. Public services are a benchmark for the performance of government agencies, and PERUMDA, as one of the BUMDs, is required to provide optimal water services to the community. Along with the times, the public bureaucracy must be more responsive and continue improving its services' quality. This study measures punctuality, service accuracy, politeness, and friendliness of employees, ease of getting services, comfort, service support facilities, and obstacles and efforts. There are still several aspects that need to be improved by PERUMDA Tirta Giri Nata Cirebon City, such as clarity of information regarding the certainty of complaint settlement time, disclosure of information regarding the certainty of complaint settlement time, and more friendly facilities for people with disabilities.